FACTORS INFLUENCING STUDENTS’ LEARNING OUTCOMES IN STATISTICAL METHODS COURSE - Ch. Ekowati Ekowati (Academic Journal of Educational Sciences, 2019)
Students’ learning outcome in a statistical methods course essentially reflects their learning effort. Indeed it is inseparable from the factors that influence it. This research was conducted to show and analyze the factors that influence students’ learning outcomes. The research subjects were 57 students of Mathematics Education Department who took the statistical methods course in 2018/2019 Academic Year. The data was collected through a questionnaire. The analytic tool used in the research is factor analysis. It is acknowledged that there are16 variables that allegedly influence students’ learning outcomes, namely: 1) mood; 2) ability to manage time; 3) relationship with family; 4) relationship with friends; 5) lecturer’s explanation; 6) residential atmosphere; 7) activities outside the course; 8) IQ; 9) financial conditions; 10) campus learning atmosphere; 11) learning style/ability to understand any teaching materials; 12) level of difficulty of the teaching materials; 13) teaching and learning facilities; 14) interest and motivation; 15) physical and health conditions; and, 16) course references. In this study, however, it was found that the learning outcomes of the students of Mathematics Education Department, Faculty of Teachers Training and Education, Nusa Cendana University, joining the statistical methods course were influenced by four main factors, that is, self-management, physical conditions, inner conditions, and learning styles.